2015
DOI: 10.1038/ncb3286
|View full text |Cite
|
Sign up to set email alerts
|

Isoform diversity in the Arp2/3 complex determines actin filament dynamics

Abstract: The Arp2/3 complex consists of seven evolutionarily conserved subunits (Arp2, Arp3 and ARPC1-5) and plays an essential role in generating branched actin filament networks during many different cellular processes. In mammals, however, the ARPC1 and ARPC5 subunits are each encoded by two isoforms that are 67% identical. This raises the possibility that Arp2/3 complexes with different properties may exist.  We found that Arp2/3 complexes containing ARPC1B and ARPC5L are significantly better at promoting actin ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
262
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(287 citation statements)
references
References 68 publications
24
262
0
1
Order By: Relevance
“…A fraction of endogenous Exo70 co-precipitated with the WRC, both without and with silencing of ARPC2. ARPC2 silencing leads to degradation of the entire Arp2/3 complex (Abella et al, 2016); depletion of ARPC1A and ARPC1B subunits was verified by western blotting (WB) (lower panels). Adaptin was detected as loading control.…”
Section: Identification Of a Forward Flow Of Wrcmentioning
confidence: 99%
See 1 more Smart Citation
“…A fraction of endogenous Exo70 co-precipitated with the WRC, both without and with silencing of ARPC2. ARPC2 silencing leads to degradation of the entire Arp2/3 complex (Abella et al, 2016); depletion of ARPC1A and ARPC1B subunits was verified by western blotting (WB) (lower panels). Adaptin was detected as loading control.…”
Section: Identification Of a Forward Flow Of Wrcmentioning
confidence: 99%
“…Indeed, W. Guo and colleagues have shown that Exo70 directly binds to the ARPC1 subunit of the Arp2/3 complex, and promotes actin branching by acting as a kinetic activator of Arp2/3 (Liu et al, 2012;Zuo et al, 2006). To directly assess a possible involvement of Arp2/3 as bridge in mediating the WRC-exocyst interaction, we treated our cells with small interfering (si)RNAs targeting the crucial subunit ARPC2, a condition known to induce degradation of the entire Arp2/3 complex (Abella et al, 2016). We verified in particular the depletion of the subunits ARPC1A and ARPC1B, which interact with Exo70.…”
Section: Exocyst and Wrc Associate In Cellsmentioning
confidence: 99%
“…The Arp2/3 complex consists of seven subunits and has been classically considered as a single molecular entity since its discovery 20 years ago. However, recent studies suggest that some subunits of the complex are dispensable in some specific cellular contexts ( [53][54][55], for review, [56]). In the case of L. monocytogenes infection, it was for example shown that the ARPC5 subunit is neither required for L. monocytogenes entry into host cells nor for actin tail formation and that the ARPC4 subunit is required for actin tail formation, probably at initial stages, but not for cell invasion [55].…”
Section: Discovery Of the Arp2/3 Complex The First Actin Nucleator Imentioning
confidence: 99%
“…In this cycle, NPF-mediated Arp2/3 complex activation is followed by branch formation, its stabilization by cortactin, and branch destabilization and filament disassembly by coronin and cofilin. In contrast to the activities exerted by NPFs and Arp2/3, functions arising from cortactin and coronin family members are not essential 7,8 , but enable cells to tune the efficiency of formation and turnover of a given Arp2/3-dependent structure. Actin disassembly, mediated for instance by cofilin family members, is expected to be essential both in vitro 2 and in vivo, but the relative functions of these proteins compared to other filament severing or disassembly factors remains to be established.…”
mentioning
confidence: 99%
“…This type of constitutive, virus-induced, actin-based motility contains only a few essential components, including N-WASP 5 and the Arp2/3 complex 7 (which likely accounts for the robustness of using this system to quantitate actin-based motility), but has the potential to be further modulated by additional actin-binding proteins in the host. Way and colleagues now report that the actin-based motility of Vaccinia virus is tuned by the isoform composition of the Arp2/3 complex, in concert with additional modulatory factors 7 .…”
mentioning
confidence: 99%